Research on highly available storage system for open virtual experiment platform. (2018) - Yan, Hui
Open teaching platform for virtual experiment can overcome some disadvantages of traditional virtual experiment systems such as heterogeneity of experiments and realise great interaction and availability. In this paper, a highly available data storage model for open virtual experiment platform is put forward, in which consistent hashing distribution, eventual consistency is used to realise this system and reading and writing control mechanism and exception handling method are adopted to ensure availability of system services. In this system, standardisation of experimental procedures and data stream are realised, based on which the efficiency of data communication is increased and development costs of virtual experiments are reduced.